Cryptocurrencies are here to Stay! Think you aren’t Vulnerable, Think Again - Blue, Levon Ellen (International Journal of Criminology and Sociology, 2025)
Cryptocurrencies are here to stay and represent a market capitalisation of approximately 3.57T. It has been reported that over 500 million people globally own cryptocurrencies. In this paper, I discuss the vulnerabilities identified with cryptocurrency ownership including who is vulnerable and then explore the role education plays. The study described involved 745 cryptocurrency owners (including 140 non-fungible token (NFT) owners) from Australia and explores the ways in which vulnerabilities play out for various demographics. The above-mentioned research revealed that almost everyone is vulnerable when it comes to cryptocurrency and/or NFT ownership and challenges who has previously been identified as experiencing financial vulnerabilities. Demographic characteristics associated with financial vulnerabilities often includes individuals with lower education levels who are living on low incomes, who identify as female and/or Indigenous and/or for whom English is a second language. It is often assumed that anyone else who does not meet the above-mentioned characteristics are assumed to be financially capable. However, with cryptocurrency ownership almost everyone is vulnerable. Education has a role to play to help combat the risks associated with cryptocurrency and/or NFT ownership. We need educators willing to teach about cryptocurrencies and NFT ownership, storage and tax implications.